2017
DOI: 10.5001/omj.2017.62
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life and Associated Factors Among Undergraduate University Students

Abstract: Young students' HRQOL is affected by socioeconomic, demographic, and behavioral factors. To improve student's HRQOL, any health-promoting strategies should focus on modifiable risk factors and socioeconomic supports for students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
1
20
2
6
Order By: Relevance
“…In addition, those between the age groups of 21 to 25 years were most likely degree students, who are expected to be more matured and can handle their life better (Macpherson, 2002), thus perceiving a better psychological quality. This result is in contrast with Nur et al, (2017) suggested that physical functioning quality had no significant difference between the age groups (less than 20 and 20 and above).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, those between the age groups of 21 to 25 years were most likely degree students, who are expected to be more matured and can handle their life better (Macpherson, 2002), thus perceiving a better psychological quality. This result is in contrast with Nur et al, (2017) suggested that physical functioning quality had no significant difference between the age groups (less than 20 and 20 and above).…”
Section: Discussioncontrasting
confidence: 99%
“…This is similar to the findings by (Klemenc-Ketis et al, 2011), where the final year students exhibited a better QoL. The university students in Turkey (Nur et al, 2017) also revealed an acceptably good QoL. Even though the total scores were found to be at a fair level, the students' ratings on their overall and general health are not worrisome.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies reported that, compared with current smokers, persons who had never smoked had significantly better health-related quality of life (HRQoL) and had less anxiety and depressive symptoms [11][12][13]. In most studies, the association of smoking with the mental health component of the HRQoL was stronger compared to that with the physical health component [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the major incremental effect obtained in relation to QALYs gained was for those had a weekly pocket money of more than €20. In relation this nding, Nur et al [31] found that young people who received an adequate amount of pocket money (understanding "adequate" similar to high) had a higher score in quality of life, speci cally in mental health. Hence, this could explain a better general HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness and cost-utility analyses were carried out for three subgroups (de ned by gender (female/male), age (< 17 years old/≥17 years old) and weekly pocket money (€0/€1 20/>€20)) due to differences found in the literature in these subgroups [7,[30][31][32]. Uncertainty was studied through multivariate deterministic sensitivity analysis of best/worst scenarios by the same subgroups mentioned above.…”
Section: Subgroup and Sensitivity Analysismentioning
confidence: 99%